Great building stories of the past - Kent, Peter (New York : Oxford University Press, 2001)
Explains the stories and principles behind some the world's greatest structures, including the Great Pyramid at Giza, the Great Wall of China, the Eiffel Tower, and the Brooklyn Bridge
Includes index
Keywords: Architecture -- Juvenile literature